Feasibility and Acceptability of a Toolkit-Based Process to Implement Patient-Centered, Immediate Postpartum Long-Acting Reversible Contraception Services. Issue 3 (March 2022) - Moniz, Michelle H.; Dalton, Vanessa K.; Smith, Roger D.; Owens, Lauren E.; Landis-Lewis, Zach; Peahl, Alex F.; Van Kainen, Barbara; Punch, Margaret R.; Wetmore, Marisa K.; Bonawitz, Kirsten; Kolenic, Giselle E.; Dehlendorf, Christine; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2021; doi: 10.1016/j.ajog.2021.10.009) It has been recommended in national guidelines that maternity systems provide patient-centered access to immediate postpartum long-acting reversible contraception (LARC). Significant barriers exist for hospitals offering these services.